2021
DOI: 10.1002/star.202100005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on Structural, Physicochemical, and In Vitro Digestive Properties of Starch from Castanopsis sclerophylla

Abstract: Annealing is a hydrothermal treatment that changes the structural and functional properties of starches. This study investigates and compares the effects of one‐step annealing for 24 and 48 h, respectively, and two‐step annealing on the structural, physicochemical, and digestive properties of Castanopsis sclerophylla starch (CaS). Annealing has no effect on CaS morphology, crystalline pattern, and short‐range ordered structures. However, annealing decreases the swelling power, solubility, setback, and peak vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
2
11
1
Order By: Relevance
“…The gelatinization characteristic curve and corresponding parameters of rice starch before and after annealing are presented in Figure 4 and Table 2 . According to Figure 4 , the peak viscosity of starch after annealing decreased by varying degrees, which was consistent with the findings of Shi et al [ 2 ]. The internal crystallization of starch increased, and the interactions between the starch chains were strengthened after annealing, thereby inhibiting the formation of hydrogen bonds between starch and water, reducing the degree of hydration in the amorphous region and limiting the swelling capacity, resulting in a decrease in peak viscosity.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The gelatinization characteristic curve and corresponding parameters of rice starch before and after annealing are presented in Figure 4 and Table 2 . According to Figure 4 , the peak viscosity of starch after annealing decreased by varying degrees, which was consistent with the findings of Shi et al [ 2 ]. The internal crystallization of starch increased, and the interactions between the starch chains were strengthened after annealing, thereby inhibiting the formation of hydrogen bonds between starch and water, reducing the degree of hydration in the amorphous region and limiting the swelling capacity, resulting in a decrease in peak viscosity.…”
Section: Resultssupporting
confidence: 91%
“…Compared with one-step annealing, the surface folds of the two-step annealed starch granules ( Figure 1 (A4,A5)) were significant, of which the surface folds of ANN−60−50 were slightly more than those of ANN−50−60, possibly resulting from the temperature changes in the two-step annealing that aggravated the dissolution of amylose in the hydrothermal effect. Shi et al [ 2 ] found that annealing at different temperatures and times had no effect on the morphology of starch from Castanopsis sclerophylla . These results showed that changes in the morphological characteristics caused by annealing modification might depend on starch source and treatment conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ] According to studies by Shi et al. [ 31 ] and Wang et al. [ 32 ] starch is not fully gelatinized, so digestibility is little affected during the process.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in firmness indicates that there was a strengthening of the bonds between the gelatinized starch granules, indicating greater interactions between amylose and amylopectin, thus forming a more stable structure and reducing amylose leaching. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%